DISCOURSE OF POWER AND POWER RELATIONS IN THE POST-MODERNITY: SOCIAL AND PHILOSOPHICAL ASPECT - Пода, Т. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article analyzes the specific features of the discourse of power and power relations under the common understanding of the concept of discourse, their common characteristics are revealed . The peculiarities of the discourse of power within the postmodern understanding. In the article is paid attention to the questions of interactions of discursive communities and authorities.